2000
DOI: 10.1038/sj.bjp.0703370
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human D1, D2(long), D2(short), D3and D4dopamine receptors by amiloride and amiloride analogues

Abstract: , Reading RG6 6AJ1 The modulatory e ects of the allosteric e ectors methylisobutylamiloride (MIA), benzamil and amiloride have been examined at human D 1 , D 2 , D 3 and D 4 dopamine receptors. The subtype selectivity and the mechanism of action of this allosteric regulation was examined. 2 In radioligand dissociation experiments each modulator accelerated dissociation from all four receptor subtypes indicating allosteric regulation. MIA displayed selectivity for the D 3 subtype for acceleration of radioligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 26 publications
2
63
0
Order By: Relevance
“…The potassium sparing diuretic amiloride has been shown to act as both an antagonist and an allosteric modulator for a number of GPCRs [41][42][43][44][45]. Other allosteric modulators (Fig.…”
Section: A 1 Arsmentioning
confidence: 99%
“…The potassium sparing diuretic amiloride has been shown to act as both an antagonist and an allosteric modulator for a number of GPCRs [41][42][43][44][45]. Other allosteric modulators (Fig.…”
Section: A 1 Arsmentioning
confidence: 99%
“…Well studied examples are D2 dopamine receptors (Hoare and Strange, 1998), muscarinic receptors (Tucek and Proska, 1995), adenosine A1 receptors (Bruns and Fergus, 1990), and ␣2-adrenergic receptors (Nunnari et al, 1987). We previously reported that aspirin and salicylic acid are allosteric inhibitors of ETA receptors (Talbodec et al, 2000).…”
mentioning
confidence: 99%
“…These modulators include SCH-202676 [21][22][23], amiloride analogues [24][25][26], agmatine [27]. The results suggested that for the P2Y 1 receptor, modes of interaction of orthosteric and allosteric binding sites might be different from that of other GPCRs.…”
Section: Discussionmentioning
confidence: 99%